2022
DOI: 10.1186/s12888-022-04410-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma complement C3 and C3a are increased in major depressive disorder independent of childhood trauma

Abstract: Background Dysregulated complement system is linked to pathophysiology of major depressive disorder (MDD). Childhood trauma has been associated with an increased incidence of adult depression via a putative mechanism of immune activation. This study aimed to measure and compare peripheral levels of complement C3, C3a, C1q and C-reactive protein (CRP) in MDD patients and healthy controls and explore the relationship between these molecule levels and childhood trauma history in the participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…Another, examining an acute phase protein response across psychiatric disorders (schizophrenia ( n = 27), mania ( n = 23), MDD ( n = 29) and healthy control ( n = 21) participants) found that C3 was significantly higher in MDD patients than controls, and in non-medicated patients compared to those taking antidepressants ( Maes et al, 1997b ). A more recent study assessing plasma C3 levels in medication-free MDD patients ( n = 49) compared to healthy controls ( n = 45), found results consistent with this ( Luo et al, 2022 ). In contrast, a large cross-sectional cross-disorder study reported significantly lower levels of C3 in MDD ( n = 1521), than in schizophrenia ( n = 1659) or bipolar disorder ( n = 1901) ( Lyu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 55%
“…Another, examining an acute phase protein response across psychiatric disorders (schizophrenia ( n = 27), mania ( n = 23), MDD ( n = 29) and healthy control ( n = 21) participants) found that C3 was significantly higher in MDD patients than controls, and in non-medicated patients compared to those taking antidepressants ( Maes et al, 1997b ). A more recent study assessing plasma C3 levels in medication-free MDD patients ( n = 49) compared to healthy controls ( n = 45), found results consistent with this ( Luo et al, 2022 ). In contrast, a large cross-sectional cross-disorder study reported significantly lower levels of C3 in MDD ( n = 1521), than in schizophrenia ( n = 1659) or bipolar disorder ( n = 1901) ( Lyu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 55%
“…The C3 and C4 play a key role in the complement cascade regulating inflammation and are particularly important in the activation of complement components. Luo et al (28) showed that the peripheral plasma concentration of C3 and C3a was significantly higher in the major depressive disorder group than in the healthy controls; Crider et al (29) showed a significant increase in C3 expression in the prefrontal cortex of depressed suicide patients, and C4A is essential for the propagation of the classical complement pathway. Genetic deficiencies of C4A are the monogenic causative factors for the prototypic autoimmune disease systemic lupus erythematosus (30); Zhou et al (31) showed that C4A deficiency is a risk factor for myositis, its subgroups and autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have demonstrated that individuals diagnosed with major depressive disorder (MDD) exhibit significantly elevated levels of various complement proteins, including C1, C1q, C3, and C3a, in their plasma compared to healthy individuals. This observation suggests a crucial involvement of the complement system in the pathophysiological mechanisms underlying MDD [ 17 19 ]. Furthermore, there is a notable increase in mRNA levels of complement C3 in the prefrontal cortex (PFC) of individuals who have died by suicide and were diagnosed with depression [ 20 ].…”
Section: Main Bodymentioning
confidence: 99%